Supply Chain Management (SCM): The Extent of its Application and Features in the Successful Delivery of Construction Projects - Benedict, Amade (International Journal of Sustainable Construction Engineering and Technology, 2017)
This study specifically sought to identify the extent and level of awareness of and adoption of the concept of SCM, identify and evaluate key features of SCM for successful construction project delivery in Nigeria. The study adopted an exploratory research design method of investigation consisting of the quantitative and qualitative methods. A purposive and convenient sampling was deployed in selecting the sample size. A semi-structured interview, case study, personal observation and questionnaire survey was carried out in a construction firm located in Abuja. The data were analyzed using descriptive statistics; Relative Importance Index (RII) and Cronbach’s Alpha reliability test. The studies found out that majority of the respondents have not heard about the SCM concept, while a few of them have heard about it. The study further revealed the following features as key, they include; level of awareness/adoption of SCM was abysmally low. Findings from the 8 key features for successful SCM construction project delivery revealed the following; disseminating quality information across the various chains, deploying web based and other software and portals as well as the application of internet in improving the effectiveness of construction, ensuring that the level of service and price of suppliers are better, applying activity based costing and management as a performance measure via the elimination of non-value adding activities across the chain, top management needs to continually implement policies that would stimulate the interests of all and sundry, relationship management and trust building, communication and environmental pressures from specialists and other professionals about the benefits of SCM, and outlining trade finance as a pre-condition for successful supply chain finance.